2018
DOI: 10.1101/353029
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

QTL Analysis of Domestication Syndrome in Zombi Pea (Vigna vexillata), an Underutilized Legume Crop

Abstract: 2 Zombi pea (Vigna vexillata (L.) A. Rich) is an underutilized crop belonging to the genus Vigna. 3 Two domesticated forms of zombi pea are cultivated as crop plants; seed and tuber forms. The 4 cultivated seed form is present in Africa, while the cultivated tuber form is present in a very 5 limited part of Asia. Genetics of domestication have been investigated in most of cultivated 6Vigna crops by means of quantitative trait locus (QTL) mapping. In this study, we investigated 7 genetics of domestication in zo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…This notion indicates that QTL mapping analysis of complex quantitative traits in alfalfa could be challenging and that large populations will be needed [33]. Compared with other QTL mapping populations in alfalfa [12,17] and other species [34,35], the population in our study was sufficiently large for the QTL mapping of spring regrowth vigor traits.…”
Section: Discussionmentioning
confidence: 95%
“…This notion indicates that QTL mapping analysis of complex quantitative traits in alfalfa could be challenging and that large populations will be needed [33]. Compared with other QTL mapping populations in alfalfa [12,17] and other species [34,35], the population in our study was sufficiently large for the QTL mapping of spring regrowth vigor traits.…”
Section: Discussionmentioning
confidence: 95%
“…When linkage map of V. vexillata (zombi pea) developed by Dachapak et al (2018) was matched with the previous linkage maps of Vigna species, it was revealed that LGs and sequence of the markers within the Vigna species were quite similar. Majority of the QTLs for seed-related attributes in zombie pea were positioned onto LG 7, where several such QTLs were detected for V. unguiculata ssp.…”
Section: Orthologous Genes In Vigna Domesticationmentioning
confidence: 85%
“…Limited work has been reported on the DRT-associated QTLs in zombie pea. Dachapak et al (2018) evaluated genetics of 22 DRTs using F 2 mapping population derived from a cross between cultivated tuber form of V. vexillata (JP235863) and wild V. vexillata (AusTRCF66514). Several genomic rearrangements were noticed in V. vexillata when compared with LGs of other four Vigna species viz.…”
Section: Genetics and Genomics Of Domesticationmentioning
confidence: 99%
“…A domesticated strain of V. vexillata called tuber cowpea was recently discovered in Bali, Indonesia, where local farmers still cultivated tuber cowpea mainly to produce high protein edible tubers (Dachapak et al, 2018;Karuniawan, Iswandi, Heinzemann & Grüneberg, 2006). According to Iseki et al (2016), the tuber cowpea (Bali) is highly sensitive to salt stress.…”
Section: Vigna Vexillatamentioning
confidence: 99%